Application of Mudharabah and Musyarakah Financing at the Sharia Rural Banks in The City of Purwokerto - Akhmad Faozan (Postgraduate Program, State Islamic University Prof. K.H. Saifuddin Zuhri Purwokerto, 2021)
Islamic banks are financial institutions that carry out their business activities based on sharia principles. Sharia principles must be applied to contracts implemented in Islamic banks. One of the contracts applied in Islamic banks is mudharabah and musyarakah contracts. This study focuses on the discussion on how to apply mudharabah and musyarakah financing, the distribution of business profit sharing and the obstacles faced by Sharia Rural Banks in the City of Purwokerto in implementing this financing. This type of research is field research using a qualitative research approach. The author uses several methods of collection in this study, namely observation, interviews and documentation. There are three stages in qualitative data analysis, namely the data reduction stage, display data, and conclusion or verification. The results of this study indicate: First, the mechanism of mudharabah and musyarakah financing at Sharia Rural Banks in the City of Purwokerto includes the initial process, the analysis process, the approval process, and the disbursement process. Second, most of the profit sharing in mudharabah and musyarakah financing at Sharia Rural Banks in the City of Purwokerto uses an income projection that reaches 80%. The rest, using the method profit and loss sharing by 17% and revenue sharing as much as 3%. Third, the small percentage of use profit and loss sharing and revenue sharing as well as the large use of income projections due to constraints such as customers not having business financial reports, especially small customers, customers' reluctance to make business financial reports and Sharia Rural Banks in the City of Purwokerto not obliging to submit business financial reports.